Theoretical analysis of MHD Maxwell two phase nano flow subject to viscous dissipation and chemical reaction: A nonsimilar approach - Muhammad Idrees Afridi; Gurram Dharmaiah; Jupudi Lakshmi Rama Prasad; Nallapati Vedavathi (Case Studies in Thermal Engineering, 2025)
Maxwell-fluid represents the flow of polymers used in the food processing industry and the cooling of copper plates. Much research has focused on maxwell-fluid flows across stretched surfaces. This article takes a different approach by examining the impacts of the magnetic and electric force on such surfaces. We aim to understand the behaviour of non-Newtonian Maxwell hydromagnetic boundary layer flow when exposed to magnetic and electric fields. The novelty of this investigation is to construct a two-equation non-similar model. It aims to examine the momentum, thermal and mass transport of Maxwell fluid with suspended conducting nanoparticles, which incorporates viscous dissipation, chemical reaction, an external magnetic and electric field, Brownian motion and thermophoresis. Moreover, the rheological behaviours of the nanofluids are significant in defining them for convective heat transfer. The partial differential equations describe the problem, and after applying suitable transformations, it is finally transformed into a set of non-similar, nonlinear and coupled non-dimensional ordinary differential equations. To get results, the bvp4c method built within MATLAB is utilized. An analysis of pertinent parameters affecting non-Newtonian fluids and the nanophase of fluids is shown in this study. Findings show that as the strength of the inclination angle decreases, the velocity profile becomes more pronounced. The temperature field improves as the heat generation parameter rises. The dimensionless concentration tends to decrease with Brownian motion. Its potential applications include medical sciences, microelectronics, biomedicine and various industrial processes.